If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 6 + 47 = x * 11 + -8 Reorder the terms for easier multiplication: 6x + 47 = x * 11 + -8 Reorder the terms: 47 + 6x = x * 11 + -8 Reorder the terms for easier multiplication: 47 + 6x = 11x + -8 Reorder the terms: 47 + 6x = -8 + 11x Solving 47 + 6x = -8 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 47 + 6x + -11x = -8 + 11x + -11x Combine like terms: 6x + -11x = -5x 47 + -5x = -8 + 11x + -11x Combine like terms: 11x + -11x = 0 47 + -5x = -8 + 0 47 + -5x = -8 Add '-47' to each side of the equation. 47 + -47 + -5x = -8 + -47 Combine like terms: 47 + -47 = 0 0 + -5x = -8 + -47 -5x = -8 + -47 Combine like terms: -8 + -47 = -55 -5x = -55 Divide each side by '-5'. x = 11 Simplifying x = 11
| x^3-70x^2+1500x-10800=0 | | 5(y-1)=7(3+y) | | 18x^2-9x-20=0 | | b^2+3=5b-3 | | 58-6x=3x+19 | | x^2+36=100 | | 8-2a=2 | | -3-2(y+4)=3y-(4y-5) | | 12x^2+43x+36=0 | | 5(2x+n)=2(n-1) | | 47=-62 | | 10x+6x= | | 29+18=-59-3 | | 3x=5y+2 | | 3(2x-1)=11-x | | 4y-4=6-7y | | 18x-3=51 | | 18y=15(y-8) | | -4x-12=13+x | | 5m+8-2m=17+4m-3 | | 5y=x+17 | | 6m-12m=1-4 | | 40x+780=70x+1230 | | 8y-6(3y-7)=0 | | 81^-3/4 | | 20x+800=50x+1250 | | 20x+80=50x+1250 | | 6m-12m=-3 | | 12-(1/9)d=17 | | -x/3+9=1x+21 | | 3n/4-8=0 | | .6a+2=.3+4+4+4+4+1 |